Observations sur l’enrichissement lexical dans la progression vers un japonais « langue passive » pour l’interprétation de conférence - Gile, Daniel (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1988)
SummaryFew Westerners have sufficient proficiency in Japanese for conference interpretation. The major stumbling block in their acquisition of Japanese as a passive language resides in vocabulary enhancement.Japanese vocabulary consists o/wago, kango and gairaigo and their compounds. Each category has different characteristics in terms of learning. While learning gairaigo is rather easy for the Westerner, wago proves more difficult to memorize, and kango poses special problems due to the small number of distinct syllables in Japanese as opposed to the large number of kanji used.The large number of words used in Japanese compounds the difficulty, especially as compared with the acquisition of a Western language where the large proportion of words having common Greco-Latin roots that can be recognized even at first sight, reduces the number of new words that actually have to be learned.These facts provide one explanation for the difficulty Westerners have in reaching an adequate level of comprehension of Japanese for interpretation purposes. They also raise questions as to the soundness of the philosophy interpreters' schools and their methods in developing high-level linguistic skills. Up to now, this question has been dealt with on the basis of" common sense " and the instructors' personal experience. Data obtained through scientific research may significantly contribute to an improvement of the situation.